Risk Factors for Ebola Virus Persistence in Semen of Survivors in Liberia. (27th May 2022) - Dyal, Jonathan; Kofman, Aaron; Kollie, Jomah Z; Fankhauser, John; Orone, Romeo; Soka, Moses J; Glaybo, Uriah; Kiawu, Armah; Freeman, Edna; Giah, Giovanni; Tony, Henry D; Faikai, Mylene; et al.
Abstract: Background: Long-term persistence of Ebola virus (EBOV) in immunologically privileged sites has been implicated in recent outbreaks of Ebola virus disease (EVD) in Guinea and the Democratic Republic of Congo. This study was designed to understand how the acute course of EVD, convalescence, and host immune and genetic factors may play a role in prolonged viral persistence in semen. Methods: A cohort of 131 male EVD survivors in Liberia were enrolled in a case-case study. "Early clearers" were defined as those with 2 consecutive negative EBOV semen test results by real-time reverse-transcription polymerase chain reaction (rRT-PCR) ≥2 weeks apart within 1 year after discharge from the Ebola treatment unit or acute EVD. "Late clearers" had detectable EBOV RNA by rRT-PCR >1 year after discharge from the Ebola treatment unit or acute EVD. Retrospective histories of their EVD clinical course were collected by questionnaire, followed by complete physical examinations and blood work. Results: Compared with early clearers, late clearers were older (median, 42.5 years; P < .001) and experienced fewer severe clinical symptoms (median 2, P = .006). Late clearers had more lens opacifications (odds ratio, 3.9 [95% confidence interval, 1.1–13.3]; P = .03), after accounting for age, higher total serum immunoglobulin G3 (IgG3) titers ( P = .005), and increased expression of the HLA-C*03:04 allele (0.14 [.02–.70]; P = .007). Conclusions: Older age, decreased illness severity, elevated total serum IgG3 and HLA-C*03:04 allele expression may be risk factors for the persistence of EBOV in the semen of EVD survivors. EBOV persistence in semen may also be associated with its persistence in other immunologically protected sites, such as the eye. Abstract : Specific risk factors among male survivors, including decreased acute Ebola virus disease severity, intraocular lens opacifications, elevated total serum immunoglobulin G3, and expression of the HLA-C*03:04 allele, may help predict the likelihood of prolonged Ebola virus persistence in semen.